2018
DOI: 10.4314/ecajs.v23i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Delay of emergency surgical interventions in Ethiopia: Patient and health system factors

Abstract: Background: The objectives of this study were to evaluate outcomes among patients with acute abdomen and abdominal trauma who presented at either of 2 referral hospitals in Addis Ababa, Ethiopia, and to determine the factors associated with delay as well as the effects of prehospital and in-hospital delay on outcome. Methods: We conducted a 1-year prospective cross-sectional study, which included all cases of surgically treated acute abdomen and abdominal trauma admitted to St Paul General Specialized Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Accordingly, in the Oromia Region, it ranges from 21.8% to 40%, 17,35,37 28% to 49.3% in the Southern Nation, Nationalities, and People Region, 23,34 18.6% to 37.3% in the Tigray Region. 10,21,25 In the Amhara Region, only one study reported the prevalence of intestinal obstruction of 50.7% among patients with the acute abdomen, 40 37.8% in the Dire Dawa city administration, 30 and 34.6% reported by a study conducted at Addis Ababa city and Amhara Region 36 (Table 4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, in the Oromia Region, it ranges from 21.8% to 40%, 17,35,37 28% to 49.3% in the Southern Nation, Nationalities, and People Region, 23,34 18.6% to 37.3% in the Tigray Region. 10,21,25 In the Amhara Region, only one study reported the prevalence of intestinal obstruction of 50.7% among patients with the acute abdomen, 40 37.8% in the Dire Dawa city administration, 30 and 34.6% reported by a study conducted at Addis Ababa city and Amhara Region 36 (Table 4).…”
Section: Resultsmentioning
confidence: 98%
“…21,34 However, the prevalence varies from 4.3% to 34.6% among total surgical admissions. 22,36 The highest prevalence of intestinal obstruction, 50.7%, was reported from the Debre Berhan Referral Hospital, Amhara Region, 40 and the lowest prevalence, 18.6%, was reported from Suhul General Hospital, Tigray Region 21 among patients with acute abdomen. According to the administrative regions and cities, in Addis Ababa, the reported prevalence of intestinal obstruction among total surgical admission ranges from 4.3% 22 to 17.1%.…”
Section: Resultsmentioning
confidence: 98%
“…A recent report suggested that on average patients travel 284.3 km, or 28.4 h to access services at specialized hospitals in Ethiopia [16]. Surgical patients are confronted with high rates of catastrophic expenditure due to a lack of financial risk protection, further contributing to delayed care seeking behavior [21,22] and causing a substantial unmet need (approximately 5 million people) [20], with high levels of mortality and disability linked to conditions treatable through surgery. Considering this baseline, the situation was worsened by the COVID-19 pandemic.…”
Section: Surgical Care In Ethiopia Pre-conflictmentioning
confidence: 99%